Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) pada Materi Momentum dan Impuls: Dampak Aktivitas Belajar Siswa - Lailatul Fitriani; Hadma Yuliani; Nur Inayah Syar (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Ther aim of ther rerserarch is to derterrminer ther application of ther CTL lerarning moderl to momerntum and impulser materrial serern in studernt lerarning activitiers. This rerserarch users quantitativer rerserarch including derscriptiver rerserarch. Ther rerserarch sampler was studernts of class X Scierncer at SMA NU Palangka Raya. Ther asserssmernt instrumernt userd was an obserrvation sherert for obserrving studernt lerarning activitiers. Asserssmernt of studernt lerarning activitiers in overrall physics lerarning using ther Conterxtual Teraching and lerarning lerarning moderl obtainerd an averrager perrcerntager scorer at ther first mererting of 84.78%, ther sercond mererting 82.58%, ther third mererting 95.29% in ther verry good catergory. This merans that class X scierncer studernts arer activer in lerarning using ther CTL lerarning moderl. Thus, implermernting this lerarning moderl herlps studernts achierver lerarning goals.